STUDI TENTANG PENGGUNAAN TUMBUHAN OBAT OLEH MASYARAKAT SUKU MUNA DI PULAU MUNA, SULAWESI TENGGARA - Rimala Sanipurnama Kindkasman; Djoko Santosa; Nanang Fakhrudin; Akhmad Riski (Jurnal Insan Farmasi Indonesia, 2026)
The use of medicinal plants still plays an important role in traditional medicine practices in Indonesia, including in the Muna Tribe on Muna Island, Southeast Sulawesi. This research aims to identify the types of medicinal plants used, the parts of the plants used, the processing methods, and the types of diseases treated based on the local genius of the community. The research method used was snowball sampling technique, with data collection through interviews with the Muna Tribe using questionnaires. The question includes information about the type of disease, herb or single plant used, local name, part used, and the method of treatment. Each mentioned plant is then identified through a determination process to obtain its Latin name, and is documented in the form of a herbarium. The results of the study show that Muna Tribe on Muna Island, Southeast Sulawesi Province, has used as many as 29 plant species from 18 families as medicinal ingredients. The most dominant part of the plant used is the leaves. The most common method of using plants or herbs is boiled, the boiled water is drunk. This method is the most commonly applied practice by the local community in using plants as traditional medicine.